Risk of Complications in Patients Undergoing Complete Thyroidectomy. A Retrospective Study - Kokalari, Igli; Shundi, Lila; Abazaj, Erjona; Ali, Ela; Nikolla, Ledina (European Scientific Journal, ESJ, 2022)
Introduction: The main aim of this study was to determine the influence of surgery on postoperative complications in patients undergoing total thyroidectomy. Methods: Patients diagnosed with goiter and undergoing total thyroidectomy for more than ten years were retrospectively enrolled, and the main study outcomes were postoperative complications. Statistical analysis was done by chi-square and t-test with a p-value <0.05 as significant. Results A total of 116 patients with goiter were identified (mean age, 45.3 ± 8.75 years, with minimum and maximum age of 23 to 69). The most affected age with goiter resulted in 41-50 years old with 41.4% (95% CI, 37.4 to 45.8%). The majority of patients with goiter were women (85.3%), with a mean age of 47 years. After the thyroid surgery, male patients had significantly higher rates of hospital readmission than females with a risk ratio [RR] of 1.05; 95% CI [0.67–1.52], p-value = 0.02. Either hemorrhage/hematoma occurred in 4.7% and cardiopulmonary and thromboembolic events in 3.1% of the patients undergoing total thyroidectomy. In addition, either hypoparathyroidism was observed in 3.1% and temporary recurrent laryngeal nerve palsy (RLN) in 1.56%. Conclusion: The current study demonstrates that total thyroidectomy is associated with an increased rate of hemorrhagic complications. RLN palsies and hypoparathyroidism are less observed. Male patients undergoing thyroidectomy have higher rates of readmission and ICU admission. Furthermore, male patients revealed higher rates of hemorrhage and wound infection, while hypoparathyroidism or temporary recurrent laryngeal nerve palsy was more frequent among female patients.